New roles for an old giant: Novel interactions of the dystonin protein - Bhanot, Kunal (University of Ottawa (Canada), 2010)
Dystonin/Bpag1 is a large cytoskeletal plakin protein that contributes to the integrity and subcellular structure of various cell types. Loss of dystonin in mice results in neuromuscular dysfunction and early death in a mouse mutant called dystonia musculorum. The phenotype in these mice is a result of sensory neuropathy causing abnormal posturing, uncoordinated muscle movements and poor muscle tone. The multi-domain structure of dystonin isoforms allows for their participation in numerous cell-specific interactions. Previous characterization of the non-epithelial dystonin proteins has focused on the alternatively spliced N-terminal actin-binding domain and the C-terminal microtubule-binding domain. Interactions of the family-defining plakin domain, however, have not been explored in detail. We therefore hypothesised that the plakin domain of neuronal dystonin (dystonin-a) interacts with a number of cytoplasmic and nuclear proteins and ultimately determines the function of these molecules in a cell-type specific manner. To this end, a pull-down interaction approach was utilized and several candidate interacting partners were identified. The candidate partners were validated through co-immunoprecipitation, co-immunofluorescence and proximity ligation assays. Through these efforts CRMP2 and myosin IIB were identified as potential binding partners of neuronal dystonin. Additionally, MAP1B, a microtubule stabilizing protein, and c1athrin heavy chain, the major component of the c1athrin triskelion were also identified as strong interaction partners for dystonin-a. The current study proposes new avenues of exploration that may elucidate the functional role of this versatile cross-linker and highlight its involvement in the cytoskeletal and endo-exocytic pathways of the cell. We hope this will further facilitate our understanding of how cytoskeletal proteins affect and regulate various neurodegenerative disorders.
Keywords: Biology, Neuroscience.